Field notes contributed by Jeffrey B. Dankert, spring 1996 - Dankert, Jeffrey B.et al (1996)
Spring report of birds and locations contributed by Jeffrey B. Dankert. Also included is a note from Dankert suggesting the Iowa Ornithologists' Union develop a reporting form that includes the entire list of birds. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed